Analisis Kualitas Lingkungan dalam Mendukung Proper (Study Kasus di Rskj Soeprapto Provinsi Bengkulu) - Fitri, Clara; Raharjo, Mursid; Setiani, Onny (Jurnal Ilmiah Mahasiswa, 2020)
The Soeprapto Special Psychiatric Hospital (RSKJ) Bengkulu Province is a hospital that has not yet conducted a PROPER assessment. Management of environmental quality in hospitals is not yet fully in accordance with regulations. Â The PROPER of assessment is still not well understood, licensing is incomplete, lack of human resources and limited budget for environmental quality management. This study aims to identify the quality of the hospital environment in supporting PROPER at Soeprapto RSKJ Bengkulu Province. This type of research design is descriptive. The population in this study were all sections that intersect with environmental management in hospitals using purposive sampling techniques. The results showed that the assessment of the proper index at the Soeprapto RSKJ Bengkulu Province included 4 criteria and 1 assessment was more than obedience. The value of the environmental document criteria / environmental permit 100%. The water pollution control criteria 83.3%. Criteria for controlling air pollution 40%. Criteria for controlling pollution of hazardous and toxic waste 62.5% and for criteria more than 0% compliance. From the results of the assessment, it can be concluded that Soeprapto RSKJ Bengkulu Province received is in the red category, where environmental management efforts only partially achieve results consistent with the requirements of regulations.